SMALL-ANGLE NEUTRON-SCATTERING INVESTIGATION OF RODLIKE MICELLES ALIGNED BY SHEAR-FLOW - Penfold, J; Staples, E; Cummins, P (1991)
The application of small angle neutron scattering (SANS) to the study of anisotropically shaped micelles, aligned by shear flow, is discussed. A typical shear flow apparatus and the theoretical basis of the data analysis are briefly presented. Some studies on dilute rodlike micelles are used to illustrate the analysis procedure, and to introduce complications due to hindered rotation, flexibility, polydispersity, turbulence and shear induced structures. Particular attention has been focused on the role of hindered rotation. More recent experimental results on the evolution of micelle size with temperature for nonionic surfactants, and the nature of mixed nonionic-cationic micelles, will be discussed in more detail. Recent experiments on viscoelastic and interacting micellar phases will be briefly described. © 1991.